Habitat engineering by beaver benefits aquatic biodiversity and ecosystem processes in agricultural streams. (11th February 2016) - Law, Alan; McLean, Fiona; Willby, Nigel J.
Summary: Small‐scale discontinuities, formed by accumulations of wood, are recognised as a key feature of functionally intact forested streams because they promote organic matter retention, increase habitat complexity and provide flow refugia. Re‐establishing such features in physically degraded streams is therefore a common priority for restoration schemes. Ecosystem engineering by beavers in the form of dam building might offer a natural mechanism for restoring degraded streams. Despite an increase in beaver reintroductions globally, the ecosystem engineering concept has rarely been applied to restoring biodiversity and ecosystem function, especially within degraded freshwater systems. By comparing multiple beaver‐modified and unmodified sites on headwater streams draining 13 ha of pastureland in eastern Scotland, U.K., we investigated if hydromorphological changes caused by reintroduced beavers ( Castor fiber ) translate into desirable biological responses when there is a long history of physical degradation and contraction of the regional species pool due to agricultural land use. Beaver modified in‐stream habitat by constructing 10 dams, thus creating a series of interconnected dam pools. Organic matter retention and aquatic plant biomass increased (7 and 20 fold higher respectively) in beaver ponds relative to unmodified channels, consistent with the lower fluctuation in stream stage observed below a series of dams. Growing season concentrations of extractable P and NO3 were on average 49% and 43% lower respectively below a series of dams than above, although colour and suspended solids concentrations increased. Macroinvertebrate samples from beaver‐modified habitats were less taxon rich (alpha diversity on average 27% lower) than those from unmodified stream habitat. However, due to significant compositional differences between beaver versus unmodified habitats, a composite sample from all habitats indicated increased richness at the landscape scale; gamma diversity was 28% higher on average than in the absence of beaver‐modified habitat. Feeding guild composition shifted from grazer/scraper and filter feeder dominance in unmodified habitats to shredder and collector‐gatherer dominance in beaver‐created habitats. Dam building by beaver in degraded environments can improve physical and biological diversity when viewed at a scale encompassing both modified and unmodified habitats. By restoring ecosystem processes locally, it may also offer wider scale benefits, including greater nutrient retention and flood attenuation. These benefits should be evaluated against evidence of any negative effects on land use or fisheries.